A framework for determining the critical distance for construction near cliff crest considering the effects of structure-soil-structure interaction: case study of Sidmouth, UK - Ali Khosravifardshirazi; Akbar A. Javadi; Ali Johari; Mohammad Akrami (Journal of Engineering and Applied Science)
Abstract Coastal cliffs are continuously shaped by forces from waves, tides, and storm surges, leading to significant erosion and structural changes that affect both natural and built environments. Understanding how fluid dynamics, soil behaviour, and foundation performance interact is essential for resilient coastal infrastructure and sustainable land-use planning. This study introduces a new conceptual and numerical modelling framework, the Fluid-Cliff-Foundation Interaction (FCFI) model, which provides a structured approach to analysing the dynamics between hydrodynamic forces, cliff morphology, soil properties, and foundation stability. Using a location-specific case study in Sidmouth, UK, the FCFI framework is applied through numerical simulations to evaluate the performance of foundations placed at varying distances from the cliff edge. The study focuses on two foundation configurations, those located close to the cliff crest and those farther. The modelling results show that foundations within 12 m of the cliff crest experience significantly higher deformation and instability under wave loading, indicating a critical risk zone. It is also shown that foundations on hard soil enhance stability and reduce deformation in bearing structure-soil-structure interaction. These results underscore the importance of considering soil type and proximity to the cliff in the analysis and placement of coastal infrastructure. This work contributes a novel integrative methodology combining geotechnical modelling and coastal dynamics, offering a basis for identifying vulnerable zones along cliff crests where wave action has a significant impact. These insights are valuable for site-specific infrastructure planning and for informing broader coastal management strategies aimed at balancing development with environmental risk mitigation.